O debate bioético e jurídico sobre as diretivas antecipadas de vontade - Mabtum, Matheus Massaro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present study addresses the main issues concerning the Advance Health Care Directive, analyzing, from Law and Bioethic's perspective, respecting the characteristics of each approach. The aim was to demonstrate that bioethics, due to its interdisciplinary nature, has an interface with legal science, especially with Biolaw, which is responsible for regulating such interaction. This study dealt with the four bioethical principles, which are described in the Belmont Report and in the Universal Declaration on Bioethics and Human Rights. The constitutional principle of human dignity also was given a special consideration, since it is one of the main parts of the legal system. The Advance Health Care Directive is a manifestation of respect for the patient's autonomy and self-determination. This study also used the personality rights doctrine to justify the link between the doctor and the patients' will. Prolongation of life and quality of life not always are associated, and for that reason dignity must be preserved in all stages, even in life's final stage, by means of a dignified death. In several occasions the patient is kept alive, but no longer has his own life, so what happens is the expansion of the process of dying. The species of medical intervention in terminal patients were theoretically distinguished: euthanasia, dysthanasia and orthothanasia. It is understood the patients' autonomy must be preserved and that is the reason why free and informed consent must be taken into account, in order to avoid abuses or inappropriate behavior. The Advance Health Care Directive, is a gender, composed of the species Living Will, which consists on limiting the refusal to certain cares and medical treatment; and Durable Power of Attorney, through which a representative is named to accomplish its' will concerning its' health, in case of incapability of free manifestation. Therefore, due to its' characteristics, it may be considered...

O presente trabalho abordou as principais questões referentes às Diretivas Antecipadas de Vontade, fazendo uma análise sob a óptica da Bioética e do Direito, respeitando as características de cada abordagem. Buscou-se demonstrar que a bioética, em razão de sua natureza interdisciplinar, apresenta uma interface com a ciência jurídica, em especial com o Biodireito, responsável por regulamentar essa interação. Foram abordados os quatro princípios bioéticos descritos no Belmont Report e na Declaração Universal sobre Bioética e Direitos Humanos. O princípio constitucional da dignidade da pessoa humana também mereceu consideração especial, vez que compõe o núcleo axiológico do ordenamento jurídico. A Diretiva Antecipada de Vontade é a representação do respeito à autonomia e autodeterminação do paciente. Utilizou-se a doutrina dos direitos da personalidade para justificar a vinculação do médico à vontade do paciente. Prolongamento de vida e qualidade de vida nem sempre estão associados, por essa razão a dignidade deve ser preservada em todas as etapas, mesmo em sua fase final, por meio de uma morte digna. Muitas vezes o paciente é mantido vivo, mas já não possui vida, então o que se tem é a ampliação do processo de morte. Procedeu-se a distinção teórica das espécies de intervenção médica em pacientes terminais: eutanásia, distanásia, e ortotanásia. Entende-se que a autonomia do paciente deve ser preservada, razão pela qual o consentimento livre e esclarecido deve ser colhido, com o escopo de evitar abusos, ou condutas inapropriadas. A Diretiva Antecipada de Vontade é gênero, composto pelas espécies: Declarações Prévias de Vontade para o Fim da Vida, que consiste em delimitar sua recusa a determinados cuidados e tratamentos médicos; e Mandato Duradouro, pelo qual se nomeia um representante para o cumprimento de suas vontades referentes à saúde, caso esteja incapacitado de manifestá-las...
Keywords: Direito a vida - Aspectos jurídicos; Direitos humanos; Direito a morte - Aspectos jurídicos; Declaração da vontade; Bioética; Direito e biologia; Law